2012
DOI: 10.1016/j.cej.2012.09.054
|View full text |Cite
|
Sign up to set email alerts
|

Retention of mercury by low-cost sorbents: Influence of flue gas composition and fly ash occurrence

Abstract: The present study employs chars obtained from the gasification of different types of biomass as low cost sorbents of mercury at laboratory scale. The influence of gas composition and fly ash occurrence on mercury retention and oxidation by char samples was evaluated. Chars obtained from a mixture of paper and plastic waste showed mercury retention capacities similar to those obtained with a commercial activated carbon. Homogeneous mercury oxidation was mainly promoted by NO 2 and , to a certain extend, by SO 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 24 publications
3
32
0
Order By: Relevance
“…Various methods are used to explore the interaction between mercury and fly ash [6][7][8][9][10][11][12][13][14][15][16]. Among them, many authors have focused on the characterization of native fly ash and their properties of mercury retention [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Various methods are used to explore the interaction between mercury and fly ash [6][7][8][9][10][11][12][13][14][15][16]. Among them, many authors have focused on the characterization of native fly ash and their properties of mercury retention [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Jang and co-authors (Jang et al 2014) reported that in combustion, SO 2 reacts with oxidized mercury (HgCl 2 ), generating fi nally particulate mercury in a form of HgSO 4(s) . Fuente-Cuesta et al (2012) suggested that O 2 has a synergistic effect on mercury oxidation, not only affecting it directly, but also via NO 2 .…”
Section: Homogeneous Reactionsmentioning
confidence: 99%
“…The effi ciency of heterogeneous reactions taking place on the surface of fl y ash also depends on the fl ue gas composition, and particularly on the concentration of NO 2 , HCl, NO, and SO 2 (Norton et al 2003, Hower et al 2010, Fuente-Cuesta et a. 2012.…”
Section: Heterogeneous Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The emissions of mercury from thermal power stations and other combustion installations account for 55.4% of the total amount of mercury emitted in Europe in 2012 [4]. Coal fired power plants also generate Hg-loaded solid wastes [5], such as fly ashes and gypsum. These sub-products are disposed of in landfills or re-used as raw materials, with the consequent risk of being released to water or to the atmosphere.…”
mentioning
confidence: 99%